Hazardous and Radioactive Waste Treatment Technologies Handbook - Oh, Chang H. (CRC Press, 2009)
Waste technologies have developed significantly over the past ten years, yet there has been no book that reflects these changes. With detailed photos and schematic system diagrams, this book provides the latest information on current technologies in the market.